Tanah Supresif: Terminologi, Sejarah, Karakteristik, dan Mekanisme - Hadiwiyono Hadiwiyono (Jurnal Perlindungan Tanaman Indonesia, 2008)
Many definitions of the suppressive soil purposed were proposed by some authors, however in summary, suppressive soil is the soil where virulent pathogen and susceptible host exist but the population and or disease produced by the pathogen are limited, due to the biotic factors supported by some specific environmental conditions. The suppressive soil phenomena has been recognized since 100 years ago, but it was thought as an interesting field since 30 years ago, and since the year many research topics related to the suppressive soil are conducted and leading to be popular. Based on the characteristic, suppressive soil could be grouped into general suppressive involving an antagonistic microbe complex being nontransferable, and specific suppressive caused by one or some antagonistic microbe being transferable. Antagonism mechanism of the microbes involved in the suppressiveness could be through antibiosis, competision, parasitism, predatism, and induced resistance.